Pengembangan Video Pembelajaran Berbasis Think Talk Write (TTW) Pada Kemampuan Menulis Siswa Sekolah Dasar - Sepwinsyah Putra; Abdul Muktadir; Endang Widi Winarni (Jurnal Pembelajaran dan Pengajaran Pendidikan Dasar, 2022)
The research aims to develop Think Talk write (TTW) based learning videos with writing skills materials for V-grade students that can be used to improve student learning outcomes. Researchers developed TTW-based learning videos using Research and Development research methods, the development of TTW-based learning videos uses 3-D models that define, design, and develop. The feasibility of TTW-based learning videos was validated by 6 experts with an average validation score of 0.88 with material expert details worth 0.91, linguists worth 0.91 and media experts valued at 0.84. with an average based on the interpretation table aiken V validation is in the high category. The teacher's response based on the interview showed a positive response in the "very appropriate" category and the student's response to the TTW-based learning video got a score of 91%. Based on the analysis of the needs of teachers and students, analysis of the feasibility test of experts in determining the feasibility of learning media as well as the responses of teachers and students as users, it can be concluded that the TTW-based learning videos that are compiled and developed are meaningful to be used as an alternative medium for learning Indonesian language learning content. especially writing skills for fifth grade elementary school students.